Experimental of surface roughness and tool wear on coolant condition technique using Aluminium alloy 319 used in automotive industries - Zainal Ariffin, Selamat; Alias, M.; A. R., Yusoff; M. M., Rahman (AD Publications, 2017)
The present day the applications of machining part tolerances, like the automotive industries aimed to reduce the fuel consumption of their vehicle by reducing the total mass per vehicle and the method process for machining. Understanding of the interaction and significance machining parameters are important to improve the efficiency of any machining process and the accuracy part produced. The objective of this research is to analyze the machining parameters (spindle speed, depth of cut and feed rates) in a three machining conditions (dry, wet and 1.0 mm coolant nozzle size on the surface roughness and tool wear using Respond Surface Method (RSM) on the CNC Lathe machine with 2 axes movements. The synthetic soluble oils, and coated cemented carbide Al2 O3 insert were used as a workpiece material and cutting tool respectively. The result of the machining experiment for Aluminum alloy 319 was investigated to analyze the main factor affecting surface roughness using the analysis of Variance (ANOVA) method. The optimum selection of the cutting conditions effectively contributes to the increase in the productivity and reduction in the production cost; therefore almost attention is paid to this problem. In cutting process, optimization of cutting parameters is considered to be a vital tool for improvement in output quality of a product as well as reducing the overall production time. The acquired results showed that the coated cemented carbide Al2 O3 insert gives the optimum overall performance in terms of surface roughness and tool wear with the smallest orifice size coolant. The research also beneficial in minimizing the costs incurred and improving productivity of manufacturing firms using the mathematical model and equations, generated by CCD based on RSM method.